oneChannelGUI: a graphical interface to Bioconductor tools, designed for life scientists who are not familiar with R language - Remo Sanges; Francesca Cordero; Raffaele Calogero (2007)
Abstract Summary: OneChannelGUI is an add-on Bioconductor package providing a new set of functions extending the capability of the affylmGUI package. This library provides a graphical interface (GUI) for Bioconductor libraries to be used for quality control, normalization, filtering, statistical validation and data mining for single channel microarrays. Affymetrix 3′ expression (IVT) arrays as well as the new whole transcript expression arrays, i.e. gene/exon 1.0 ST, are actually implemented. oneChannelGUI is available for most platforms on which R runs, i.e. Windows and Unix-like machines. Availability: http://www.bioconductor.org/packages/2.0/bioc/html/oneChannelGUI.html Contact: raffaele.calogero@unito.it Supplementary information: http://www.bioinformatica.unito.it/oneChannelGUI/